Determinants of biogas adoption in manure management of Vietnamese household pig production: A case study in Tien Lu District, Hung Yen Province - Nguyen Thi Ly; Nanseki, T.; Chomei, Y. (2015)
Although biogas technology is one of the useful ways managing the animal manure to reduce environmental problems in rural area, many Vietnamese households that produce pigs still do not apply biogas digesters. This study aim to investigate the main factors contributing to biogas adoption in household pig production based on primary data collected in Tien Lu district, Hung Yen province in Vietnam and the use of Logit regression. The empirical results highlighted that socioeconomic characteristics of household pig productions were differed between biogas adoption group and biogas non–adoption group among them, including household heads’ membership status (joined in farmer groups), training and education, medium and large farm size. Moreover, the results suggested that the probability of biogas adoption of household pig production increases with an increase of household heads’ schooling years and households’ income except for a case that when the former is higher than 10.5 or when the latter is more than 192.8 million VND. Also this probability increase with household heads are memberships and with large household farm size. Educational and awareness programs on the merits of biogas digester, particularly via the channels among farmers should be implemented. Furthermore, financial program should be offered to farmers especially to low income households.